Immunomodulatory potential of chitosan-based materials for cancer therapy: a systematic review of in vitro, in vivo and clinical studies. (29th March 2021) - Lima, Beatriz V.; Oliveira, Maria J.; Barbosa, Mário A.; Gonçalves, Raquel M.; Castro, Flávia
Abstract : Chitosan (Ch) has recently been used in different studies as an immune adjuvant with ability to modulate the tumor microenvironment (TME). Abstract : Chitosan (Ch) has recently been used in different studies as a vaccine adjuvant with an ability to modulate the tumor microenvironment (TME). This systematic review aims to elucidate the added value of using Ch-based therapies for immunotherapeutic strategies in cancer treatment, through the exploration of different Ch-based formulations, their capacity to modulate immune cells in vitro and in vivo, and their translational potential for clinical settings. A systematic review was conducted on PubMed, following both inclusion and exclusion steps. Original articles which focused on the immunomodulatory role of Ch-based formulations in the TME were included, as well as its usage as a delivery vehicle for other immunomodulatory molecules. This review illustrates the added value of Ch-based systems to reshape the TME, through the modulation of immune cells using different Ch formulations, namely solutions, films, gels, microneedles and nanoparticles. Generally, Ch-based formulations increase the recruitment and proliferation of cells associated with pro-inflammatory abilities and decrease cells which exert anti-inflammatory activities. These effects correlated with a decreased tumor weight, reduced metastases, reversion of the immunosuppressive TME and increased survival in vivo . Overall, Ch-based formulations present the potential for immunotherapy in cancer. Nevertheless, clinical translation remains challenging, since the majority of the studies use Ch in formulations with other components, implicating that some of the observed effects could result from the combination of the individual effects. More studies on the use of different Ch-based formulations, complementary to standardization and disclosure of the Ch properties used are required to improve the immunomodulatory effects of Ch-based formulations in cancer.